A Co7Fe3 / Mo2C@C composite material for oxygen evolution catalyst at the anode of water electrolysis and its preparation method

CN117661019BActive Publication Date: 2026-10-09WUHAN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311657480.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-04
Publication Date
2026-10-09
Estimated Expiration
2043-12-04

AI Technical Summary

Technical Problem

通常情况下,HER和OER反应较高的过电位导致电解水产氢的能耗高,成本昂贵,限制了电解水制氢技术在工业生产中的广泛应用

Benefits of technology

[0016] (1) This invention utilizes polyvinylpyrrolidone (PVP) and (NH4)6Mo7O 24 Using Co(NO3)2·6H2O and Fe(NO3)3·9H2O as raw materials and deionized water as solvent, a Co7Fe3/Mo2C@C composite material was prepared through a one-step high-temperature reaction. This invention synthesizes a composite material of Co7Fe3 alloy, Mo2C, and C through an in-situ reaction in one step. Mo2C is used to regulate the electronic structure of the Co7Fe3 alloy, reducing the OER overpotential and thus improving the oxygen evolution reaction performance of the Co7Fe3 alloy. Therefore, the Co7Fe3/Mo2C@C composite material can be used as a highly efficient anolyte oxygen evolution catalyst in water electrolysis for hydrogen production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117661019B_ABST
    Figure CN117661019B_ABST
Patent Text Reader

Abstract

The application discloses an electrolytic water anode oxygen evolution catalyst Co7Fe3 / Mo2C@C composite material and a preparation method thereof. 24 The application uses PVP, (NH4)6Mo7O 24 , Co(NO3)2.6H2O and Fe(NO3)3.9H2O as raw materials, and synthesizes the Co7Fe3 / Mo2C@C composite material through in-situ reaction in one step, uses Mo2C to regulate the electronic structure of the Co7Fe3 alloy, reduces the OER overpotential, and thus improves the catalytic oxygen evolution performance of the Co7Fe3 alloy catalyst, so that the Co7Fe3 / Mo2C@C composite material can be applied to electrolytic water hydrogen production as a high-efficiency anode oxygen evolution catalyst. The preparation method realizes in-situ generation of the carbon base, Co7Fe3 and Mo2C in the Co7Fe3 / Mo2C@C composite material, realizes effective regulation of the electronic structure of the Co7Fe3 alloy catalyst and the catalytic performance of Mo2C while better conductivity is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of catalytic material synthesis technology, and specifically relates to a Co7Fe3 / Mo2C@C composite material for an anode oxygen evolution catalyst in water electrolysis and its preparation method. Background Technology

[0002] Electrolysis of water is an important green and sustainable method for hydrogen production, involving two half-reactions: hydrogen evolution reaction (HER) at the cathode and oxygen evolution reaction (OER) at the anolyte. Typically, the high overpotentials of both HER and OER reactions lead to high energy consumption and high costs, limiting the widespread industrial application of this technology. In contrast, the OER reaction, due to its multi-electron characteristics, exhibits slower reaction kinetics and a significantly higher overpotential than the HER reaction at the cathode. Therefore, developing low-cost, highly active OER catalysts to reduce the OER overpotential is crucial for improving the efficiency of water electrolysis and reducing energy costs.

[0003] Currently, inexpensive and readily available cobalt-iron alloys exhibit high catalytic activity in the OER reaction, but their catalytic performance still lags significantly behind that of commercial IrO2 catalysts. Therefore, this invention proposes a one-step in-situ synthesis of a composite material of Co7Fe3 alloy, Mo2C, and C. Mo2C is used to modulate the electronic structure of the Co7Fe3 alloy, thereby enhancing its catalytic activity, reducing the overpotential of the OER, and improving the oxygen evolution performance of the cobalt-iron alloy catalyst. This provides a new approach for improving the efficiency of OER cobalt-iron alloy catalysts in water electrolysis for hydrogen production, and is of great significance for reducing the cost of water electrolysis for hydrogen production and promoting its widespread application. Summary of the Invention

[0004] To address the problems existing in the prior art, this invention provides a Co7Fe3 / Mo2C@C composite material for an anode oxygen evolution catalyst in water electrolysis and its preparation method.

[0005] The first aspect of this invention provides a method for preparing a Co7Fe3 / Mo2C@C composite material for an anode oxygen evolution catalyst in water electrolysis, comprising the following steps:

[0006] S1. Polyvinylpyrrolidone (PVP) and (NH4)6Mo7O 24 Co(NO3)2·6H2O and Fe(NO3)3·9H2O were dissolved in deionized water, stirred evenly, and the mixture was dried and ground after the solvent was evaporated.

[0007] S2. The ground mixture is placed in a tube furnace and reacted at high temperature under N2 atmosphere to obtain Co7Fe3 / Mo2C@C composite material.

[0008] Preferably, in step S1, the polyvinylpyrrolidone (PVP) and (NH4)6Mo7O 24 The mass ratio of Co(NO3)2·6H2O and Fe(NO3)3·9H2O is 5:0.2~1:0.4~5:0.6~2.

[0009] Preferably, in step S1, the stirring is carried out at room temperature for 2 to 5 hours.

[0010] Preferably, in step S1, the temperature of the evaporating solvent is 75–95°C.

[0011] Preferably, in step S1, the drying temperature is 80–95°C.

[0012] Preferably, in step S2, the heating rate is 8-10℃ / min, the calcination temperature is 600-900℃, and the calcination time is 2-4h.

[0013] A second aspect of the present invention provides a Co7Fe3 / Mo2C@C composite material for an anode oxygen evolution catalyst in water electrolysis prepared by the above-described preparation method.

[0014] A third aspect of the present invention provides the application of the above-mentioned Co7Fe3 / Mo2C@C composite material for the anode oxygen evolution catalyst in water electrolysis in hydrogen production.

[0015] The present invention has the following beneficial effects:

[0016] (1) This invention utilizes polyvinylpyrrolidone (PVP) and (NH4)6Mo7O 24 Using Co(NO3)2·6H2O and Fe(NO3)3·9H2O as raw materials and deionized water as solvent, a Co7Fe3 / Mo2C@C composite material was prepared through a one-step high-temperature reaction. This invention synthesizes a composite material of Co7Fe3 alloy, Mo2C, and C through an in-situ reaction in one step. Mo2C is used to regulate the electronic structure of the Co7Fe3 alloy, reducing the OER overpotential and thus improving the oxygen evolution reaction performance of the Co7Fe3 alloy. Therefore, the Co7Fe3 / Mo2C@C composite material can be used as a highly efficient anolyte oxygen evolution catalyst in water electrolysis for hydrogen production.

[0017] (2) The preparation method of this invention achieves in-situ composite formation of carbon substrate, Co7Fe3, and Mo2C in the Co7Fe3 / Mo2C@C composite material, achieving both good electrical conductivity and effective regulation of the electronic structure and catalytic performance of the Co7Fe3 alloy catalyst by Mo2C. The preparation method of this invention is simple, requiring only one reaction step to obtain a highly efficient Co7Fe3 / Mo2C@C oxygen evolution catalyst material, which saves costs and facilitates widespread application. Attached Figure Description

[0018] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0019] Figure 1 The XRD pattern of the Co7Fe3 / Mo2C@C composite material prepared in Example 1;

[0020] Figure 2 The EDX spectrum of the Co7Fe3 / Mo2C@C composite material prepared in Example 1;

[0021] Figure 3 Linear sweep voltammetry (LSV) curves of Co7Fe3 / Mo2C@C composite materials, Co7Fe3@C, and Mo2C@C prepared in Examples 1 and Comparative Examples 1-2;

[0022] Figure 4 The graph shows the stability (IT) results of the Co7Fe3 / Mo2C@C composite material prepared in Example 1 in 1M KOH electrolyte;

[0023] Figure 5 The fine XPS spectrum of the Co7Fe3 / Mo2C@C composite material prepared in Example 1;

[0024] Figure 6 This is a schematic diagram of the reaction energy barriers at each step in the kinetic reaction process of the Co7Fe3 / Mo2C@C composite material and Co7Fe3@C. Detailed Implementation

[0025] In the following description, specific details such as particular system structures and techniques are set forth for illustrative purposes and not for limitation, in order to provide a thorough understanding of the embodiments of the present invention. However, those skilled in the art will understand that the present invention may also be implemented in other embodiments without these specific details. The present invention will now be described in detail with reference to embodiments.

[0026] Example 1

[0027] (1) Accurately measure 20 mL of deionized water into a beaker, place the beaker on a magnetic stirrer, and while stirring, add 0.5 g of polyvinylpyrrolidone (PVP) and 0.0265 g of (NH4)6Mo7O in sequence. 240.1019g Co(NO3)2·6H2O and 0.0606g Fe(NO3)3·9H2O were stirred at room temperature for 3 hours, and then the solvent was evaporated by stirring in an 80°C water bath. After the solvent was evaporated to dryness, the mixture was transferred to an oven and dried at 90°C overnight.

[0028] (2) After drying, the mixture is ground and then transferred to a tube furnace. Under N2 atmosphere, the temperature is increased to 800℃ at a heating rate of 10℃ / min and held for 2 hours. The mixture is then naturally cooled to room temperature to obtain the Co7Fe3 / Mo2C@C composite material.

[0029] Example 2

[0030] (1) Accurately measure 20 mL of deionized water into a beaker, place the beaker on a magnetic stirrer, and while stirring, add 0.5 g of polyvinylpyrrolidone (PVP) and 0.0353 g of (NH4)6Mo7O in sequence. 24 0.1019g Co(NO3)2·6H2O and 0.0606g Fe(NO3)3·9H2O were stirred at room temperature for 3 hours, and then the solvent was evaporated by stirring in an 80°C water bath. After the solvent was evaporated to dryness, the mixture was transferred to an oven and dried at 90°C overnight.

[0031] (2) After drying, the mixture is ground and then transferred to a tube furnace. Under N2 atmosphere, the temperature is increased to 800℃ at a heating rate of 10℃ / min and held for 2 hours. The mixture is then naturally cooled to room temperature to obtain the catalyst composite material.

[0032] Example 3

[0033] (1) Accurately measure 20 mL of deionized water into a beaker, place the beaker on a magnetic stirrer, and while stirring, add 0.5 g of polyvinylpyrrolidone (PVP) and 0.0265 g of (NH4)6Mo7O in sequence. 24 0.0437g Co(NO3)2·6H2O and 0.0606g Fe(NO3)3·9H2O were stirred at room temperature for 3 hours, and then the solvent was evaporated by stirring in an 80°C water bath. After the solvent was evaporated to dryness, the mixture was transferred to an oven and dried at 95°C overnight.

[0034] (2) After drying, the mixture is ground and then transferred to a tube furnace. Under N2 atmosphere, the temperature is increased to 800℃ at a heating rate of 8℃ / min and held for 2 hours. The mixture is then naturally cooled to room temperature to obtain the catalyst composite material.

[0035] Example 4

[0036] (1) Accurately measure 20 mL of deionized water into a beaker, place the beaker on a magnetic stirrer, and while stirring, add 0.5 g of polyvinylpyrrolidone (PVP) and 0.0265 g of (NH4)6Mo7O in sequence. 24 0.2038g Co(NO3)2·6H2O and 0.0606g Fe(NO3)3·9H2O were stirred at room temperature for 3 hours, and then the solvent was evaporated by stirring in a water bath at 75°C. After the solvent was evaporated to dryness, the mixture was transferred to an oven and dried at 95°C overnight.

[0037] (2) After drying, the mixture is ground and then transferred to a tube furnace. Under N2 atmosphere, the temperature is increased to 600℃ at a heating rate of 10℃ / min and held for 4 hours. The mixture is then naturally cooled to room temperature to obtain the catalyst composite material.

[0038] Example 5

[0039] (1) Accurately measure 20 mL of deionized water into a beaker, place the beaker on a magnetic stirrer, and while stirring, add 0.5 g of polyvinylpyrrolidone (PVP) and 0.0265 g of (NH4)6Mo7O in sequence. 24 0.1019g Co(NO3)2·6H2O and 0.1414g Fe(NO3)3·9H2O were stirred at room temperature for 5 hours, and then the solvent was evaporated by stirring in a water bath at 95℃. After the solvent was evaporated to dryness, the mixture was transferred to an oven and dried at 90℃ overnight.

[0040] (2) After drying, the mixture is ground and then transferred to a tube furnace. Under N2 atmosphere, the temperature is increased to 900℃ at a heating rate of 10℃ / min and held for 2 hours. The mixture is then naturally cooled to room temperature to obtain the catalyst composite material.

[0041] Comparative Example 1

[0042] (1) Accurately measure 20 mL of deionized water into a beaker, place the beaker on a magnetic stirrer, and while stirring, add 0.5 g of polyvinylpyrrolidone (PVP) and 0 g of (NH4)6Mo7O in sequence. 24 0.1019g Co(NO3)2·6H2O and 0.0606g Fe(NO3)3·9H2O were stirred at room temperature for 3 hours, and then the solvent was evaporated by stirring in an 80°C water bath. After the solvent was evaporated to dryness, the mixture was transferred to an oven and dried at 90°C overnight.

[0043] (2) After drying, the mixture is ground and then transferred to a tube furnace. Under N2 atmosphere, the temperature is increased to 800℃ at a heating rate of 10℃ / min and held for 2 hours. The mixture is then naturally cooled to room temperature to obtain Co7Fe3@C material.

[0044] Comparative Example 2

[0045] (1) Accurately measure 20 mL of deionized water into a beaker, place the beaker on a magnetic stirrer, and while stirring, add 0.5 g of polyvinylpyrrolidone (PVP) and 0.0265 g of (NH4)6Mo7O in sequence. 24 0g Co(NO3)2·6H2O and 0g Fe(NO3)3·9H2O were stirred at room temperature for 3 hours, and then the solvent was evaporated by stirring in an 80°C water bath. After the solvent was evaporated to dryness, the mixture was transferred to an oven and dried at 90°C overnight.

[0046] (2) After drying, the mixture is ground and then transferred to a tube furnace. Under N2 atmosphere, the temperature is increased to 800℃ at a heating rate of 10℃ / min and held for 2 hours. The mixture is then naturally cooled to room temperature to obtain Mo2C@C material.

[0047] (a) The Co7Fe3 / Mo2C@C composite material prepared in Example 1 was characterized. The XRD and EDX results are shown in the figure. Figure 1 and Figure 2 .

[0048] Depend on Figure 1 The results show that the Co7Fe3 / Mo2C@C composite material prepared in Example 1 contains Co7Fe3 alloy, Mo2C and C.

[0049] Depend on Figure 2 The results show that the material prepared in Example 1 contains Co, Fe, Mo, C and O elements; the above XRD and EDX characterization results show that the Co7Fe3 / Mo2C@C composite material was successfully prepared by the present invention.

[0050] (b) The electrocatalytic activity of the Co7Fe3 / Mo2C@C composite material prepared in Example 1 was tested, and the results are shown in [the table below]. Figure 3 .

[0051] The electrocatalytic OER activities of Co7Fe3 / Mo2C@C, Mo2C@C, and Co7Fe3@C catalysts in 1.0 M KOH electrolyte were tested using linear sweep voltammetry (LSV). The electrocatalytic OER activities of the three catalysts, Co7Fe3 / Mo2C@C, Co7Fe3@C, and Mo2C@C, at 10 mA / cm² were [not specified in the original text]. 2 The overpotentials at current densities were 254 mV, 308 mV, and 439 mV, respectively. The Co7Fe3 / Mo2C@C composite material at 10 mA / cm²... 2 The overpotential at current density is 185 mV lower than that of Mo2C@C and 54 mV lower than that of Co7Fe3@C. These results indicate that the introduction of Mo2C can effectively improve the OER catalytic performance of the Co7Fe3 alloy.

[0052] (c) The catalytic stability of the Co7Fe3 / Mo2C@C composite material prepared in Example 1 was tested, and the results are shown in [the table below]. Figure 4 .

[0053] Figure 4 The results showed that the current density did not decrease significantly after a long catalytic experiment (20 h), and the Co7Fe3 / Mo2C@C composite material prepared in Example 1 exhibited excellent catalytic stability.

[0054] (d) XPS fine spectroscopy was performed on the Co7Fe3 / Mo2C@C composite material prepared in Example 1. The results are shown in [the table below]. Figure 5 Then, kinetic reaction energy barriers were tested on the Co7Fe3 / Mo2C@C composite material and Co7Fe3@C. The results are shown in [Figure number missing]. Figure 6 .

[0055] Figure 5 The XPS results (a)-(d) show that Co is present in both Co7Fe3 / Mo2C@C and Co7Fe3@C. 3+ and Co 2+ Fe also exists in two valence states. 2+ and Fe 3+ Two valence states; comparing Co and Fe in Co7Fe3 / Mo2C@C and Co7Fe3@C, it can be found that when Mo2C is introduced into Co7Fe3@C, the electronic structure of Co and Fe in Co7Fe3 / Mo2C@C undergoes a significant positive shift compared to Co7Fe3@C; further comparing Co7Fe3 / Mo2C@C and Mo2C@C, it is found that after introducing Mo2C into Co7Fe3@C, the electronic structure of Mo undergoes a significant negative shift. This indicates that in Co7Fe3 / Mo2C@C, electrons are transferred from Co and Fe to Mo. This proves that Mo2C effectively regulates the electronic structure of Co7Fe3 alloy, and this effective regulation is beneficial to improving the catalytic performance of the OER reaction of cobalt-iron alloy.

[0056] Depend on Figure 6 The results show that, compared with Co7Fe3@C, the reaction energy barrier of the Co7Fe3 / Mo2C@C composite material is effectively reduced in the catalytic OER reaction. Specifically, the rate-determining step of Co7Fe3@C is: *O2 + H2O + 4e- - →O2 + 2H2O + 4e - +*, the calculated free energy for this step is 3.40 eV, while the rate-determining step for Co7Fe3 / Mo2C@C is: *O + 2OH - +H₂O + 2e - →*OOH+OH - +H₂O + 3e- The calculated free energy for this step is 2.43 eV. Clearly, the calculated free energy of the rate-determining step of Co7Fe3 / Mo2C@C (2.43 eV) is significantly lower than that of the rate-determining step of Co7Fe3@C (3.40 eV). This indicates that the introduction of Mo2C can effectively regulate the electronic structure of the cobalt-iron alloy while accelerating electron transfer in the reaction process, lowering the reaction energy barrier of the kinetic reaction, and thus achieving the technical effect of reducing the overpotential of the OER reaction.

[0057] This invention is not limited to the specific embodiments described above. Any modifications made by those skilled in the art based on the above concept without creative effort are within the scope of protection of this invention.

Claims

1. A method for preparing a Co7Fe3 / Mo2C@C composite material for an anode oxygen evolution catalyst in water electrolysis, comprising the following steps: S1. Polyvinylpyrrolidone (PVP) and (NH4)6Mo7O 24 Co(NO3)2·6H2O and Fe(NO3)3·9H2O are dissolved in deionized water, stirred evenly, and the mixture is dried and ground after the solvent is evaporated; the temperature of solvent evaporation is 75~95℃. S2. The ground mixture is placed in a tube furnace and calcined under a N2 atmosphere to obtain the Co7Fe3 / Mo2C@C composite material; the calcination temperature is 600~900℃.

2. The method for preparing the Co7Fe3 / Mo2C@C composite material for the anode oxygen evolution catalyst in water electrolysis according to claim 1, characterized in that, In step S1, the polyvinylpyrrolidone, (NH4)6Mo7O 24 The mass ratio of Co(NO3)2·6H2O and Fe(NO3)3·9H2O is 5:0.2~1:0.4~5:0.6~2.

3. The method for preparing the Co7Fe3 / Mo2C@C composite material for the anode oxygen evolution catalyst in water electrolysis according to claim 1, characterized in that, In step S1, the stirring is carried out at room temperature for 2 to 5 hours.

4. The method for preparing the Co7Fe3 / Mo2C@C composite material for the anode oxygen evolution catalyst in water electrolysis according to claim 1, characterized in that, In step S1, the drying temperature is 80~95℃.

5. The method for preparing the Co7Fe3 / Mo2C@C composite material for the anode oxygen evolution catalyst in water electrolysis according to claim 2, characterized in that, In step S2, the heating rate is 8~10℃ / min, and the calcination time is 2~4h.

6. A Co7Fe3 / Mo2C@C composite material for an anode oxygen evolution catalyst in water electrolysis, prepared by the method described in any one of claims 1-5.

7. The application of the Co7Fe3 / Mo2C@C composite material of the anode oxygen evolution catalyst for water electrolysis as described in claim 6 in hydrogen production by water electrolysis.